Effect of substrate orientation on the optical properties of InGaAsN(P) quantum wells - Marta Gladysiewicz; M. S. Wartak (APL Quantum)
This study examines the effect of substrate orientation on the optical properties of InGaAsN(P) quantum wells using an eight-band k · p Hamiltonian extended to account for strain effects in arbitrary orientations. Numerical simulations were performed for key substrate orientations, including (001), (110), (111), and (112), with particular focus on the impact of strain-induced piezoelectric fields on band alignment and wavefunction localization. The results reveal substantial differences in the band structure, wavefunctions, absorption coefficients, and material gain across the studied orientations. The (111) orientation exhibits the strongest piezoelectric fields, leading to enhanced confinement and the formation of additional bound states in the conduction band. Band structure analysis indicates significant strain-induced variations in the bandgap and energy levels, particularly in non-(001) orientations. In addition, the absorption coefficient strongly depends on the substrate orientation. The (111) and (001) orientations exhibit the highest absorption coefficient values, making them strong candidates for solar cell applications. Other orientations may be more suitable for laser applications due to their high material gain values.